DIGITAL LITERACY TRAINING FOR AMANAH HOLISTIC KINDERGARTEN TEACHERS, EAST SEMARANG: TRAINING LITERASI DIGITAL BAGI GURU TK HOLISTIK AMANAH, SEMARANG TIMUR - Wili Astuti; Yayan Mahfuzin; Muhamad Taufik Hidayat (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2023)
Education is an important factor in the development of a nation. In today's digital era, digital literacy skills are becoming increasingly important for all levels of society, including for teachers and especially for children. The aim to be achieved through this service activity is to provide digital literacy training and improve digital literacy skills for Amanah Holistik Kindergarten teachers to serve children's learning. This community service activity was attended by 10 teachers of Amanah Holistik Kindergarten on March 25, 2023. This community service activity is carried out in the form of training with stages (1) Exposure, Discussion and Q&A (2) Practice. There are two aspects assessed in this activity (1) Participant activities during training. (2) The level of mastery of the training material. The results of the service activities for Amanah Holistic Kindergarten teachers, namely by making a positive contribution to efforts to improve the quality of education, especially the skills of introducing digital literacy. Based on the evaluation results, this activity is considered successful because 100% of the participants participated in the activity and mastered the training material.